Pengaruh Motivasi Berwirausaha, Faktor Lingkungan Dan Mental Terhadap Minat Berwirausaha Mahasiswa (Studi Pada Mahasiswa UNISMA Angkatan 2020) - Amalia, Annisa Luthfi; Salim, Muhammad Agus; Slamet, Afi Rahmat (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the influence of entrepreneurial motivation, environmental and mental factors on students' entrepreneurial interest. The population in this study were students at the Islamic University of Malang Class of 2020 who had taken entrepreneurship courses. This research uses a quantitative type of research, with a sampling method using a purposive sampling technique which is used based on certain criteria using a questionnaire distributed to 96 respondents. With the results of the multiple linear regression test, entrepreneurial motivation and environmental factors have a positive effect on students' interest in entrepreneurship, while mental health has a negative effect on students' interest in entrepreneurship. Based on the results of hypothesis testing, it is known that simultaneously entrepreneurial motivation, environmental and mental factors have a significant influence on students' entrepreneurial interest, partially entrepreneurial motivation, environmental and mental factors have a significant influence on students' entrepreneurial interest. Entrepreneurial motivation, environmental and mental factors contributed 71.5% to students' entrepreneurial interest. Keywords: Entrepreneurial Motivation, Environmental Factors, and Mentality